Jim Crow and Black Economic Progress after Slavery - Althoff, Lukas; Reichardt, Hugo (Quarterly Journal of Economics, 2024)
Abstract This article studies the long-run effects of slavery and restrictive Jim Crow institutions on Black Americans’ economic outcomes. We track individual-level census records of each Black family from 1850 to 1940 and extend our analysis to neighborhood-level outcomes in 2000 and surname-based outcomes in 2023. We show that Black families whose ancestors were enslaved until the Civil War have considerably lower education, income, and wealth than Black families whose ancestors were free before the Civil War. The disparities between the two groups have persisted substantially because most families enslaved until the Civil War lived in states with strict Jim Crow regimes after slavery ended. In a regression discontinuity design based on ancestors’ enslavement locations, we show that Jim Crow institutions sharply reduced Black families’ economic progress in the long run.